'A literary phenomenon of the non-literate': classed cultural value, agency and techniques of self-representation in the ghostwritten reality TV star memoir. Issue 3 (2nd July 2016) - Yelin, Hannah
ABSTRACT: The wide readership and commercial power of the ghostwritten celebrity memoir are indicative of its cultural significance, yet it remains a critically overlooked, much-derided genre. With some of the most popular texts being associated with female celebrities, both the books and their female author-subjects are 'bad objects': viewed as inauthentic due to visible mediation and thus denied authority. This article seeks to demonstrate that, far from being a legitimate means by which to invalidate the genre, the ghostwritten status of celebrity memoir is a source of complexity that rewards critique, and, indeed, makes it an exemplary site for the study of the wider dynamics of the construction and circulation of celebrity. This reading accounts for both the collaborative authorship and the industrial conditions of these texts' construction without dismissing them as the solely cynical manufacture of corporate merchandise. Contrasting the memoirs of Paris Hilton and Jade Goody (and their respective ghostwriters where visible) offers a productive interplay between polar class positions that enables a reading of the ways in which access to certain capitals inflects the celebrity's status as subject of her own life story. This shows the ways in which agency in self-representation is multiple and negotiated within gendered parameters.